Multi-resolution analysis for high-fidelity deconvolution microscopy - Baolei Liu; Fan Wang (Light: Science & Applications)
Abstract A fidelity-ensured multi-resolution analysis deconvolution algorithm significantly enhances fluorescence microscopy’s resolution and noise control, enabling more accurate and detailed imaging for advanced biological research applications.